Kohtuuhintaisen asumisen hajanainen kokonaisuus - Elina Sutela; Sampo Ruoppila; Jarkko Rasinkangas; Jutta Juvenius (Yhdyskuntasuunnittelun seura ry., 2022)
The article analyses how housing affordability is defined in Finnish housing policy. The data consists of laws, policy documents and expert interviews. Three theoretical approaches are identified: normative definitions, consumer choice and definition by housing tenure. Normative definitions that consider affordability as an intersection of household income, housing costs and housing standards are acknowledged, but not treated as policy objectives. Nevertheless, housing allowances are a practical implementation of this approach. The main aim of housing policy – increasing housing supply to support a balanced market – implies that the housing question is to be solved primarily by the market and, consequently, affordability is defined by consumer choice. Social rental housing is often explicitly referred to as “affordable”. However, limiting the question to one tenure is problematic. The article recommends adopting a normative definition as well as better coordination of housing policy, which is now divided between different ministries.